Células T regulatórias (FoxP3+) e sua relação com parâmetros clínico-patológicos em carcinomas de células escamosas de lábio inferior – Estudo imunoistoquímico - Cunha Filho, Fernando Antônio Portela da (2015)
The squamous cell carcinoma (SCC) of lower lip is one of the most common malignancies of the head and neck region. Nevertheless, several aspects related to the progression of this lesion remain incompletely understood. Evidence shows that regulatory T cells (Tregs) play a major role in the suppression of the activity of various immune system cells, they may be involved in tumor progression and associated with the most aggressive biological behavior of various tumors. Despite these findings, there are few studies about the presence of these cell types in the SCC of lower lip. The objective of this study was to evaluate, through immunohistochemistry, the amount of Tregs cells (FoxP3+) in the microenvironment of SCCs of the lower lip and to relate this with clinicopathological parameters (tumor size / extent, regional nodal metastasis, distant metastasis, clinical stage and histopathological grade of malignancy). The sample consisted of 50 cases of SCC of the lower lip. Clinical data were obtained from medical records of patients and the histopathological grade of malignancy of the lesion was evaluated in the invasive front, according to the system proposed by Bryne et al. (1992). For the immunohistochemical study, lymphocytes exhibiting nuclear positivity for FoxP3 were counted in 10 microscopic fields at the tumor invasive front and the mean value was calculated for each case. Comparisons of the medians of Tregs cells according to clinicopathological parameters were performed using the nonparametric Mann-Whitney test. Possible associations between histopathological grade of malignancy and clinical parameters were analyzed by Fisher's exact test. The level of significance was set at 5% (p < 0.05). Most SCCs of the lower lip without regional nodal metastasis (n = 17; 81.0%) were classified as lowgrade malignancy (p < 0.001). In turn, the majority of patients in stages III and IV (n = 22; 84.6%) had high-grade tumors (p < 0.001). FoxP3+ lymphocytes were observed in all cases evaluated, with a tendency for higher amounts of these cell types, although not statistically significant, in lesions of small size, without regional nodal metastasis, and in early clinical stages (p > 0.05). Low-grade malignancy lesions revealed higher amount of FoxP3+ lymphocytes in comparison with high-grade tumors (p = 0.019), with medians of 16.00 and 6.60, respectively. Tumors with intense inflammatory infiltrate exhibited higher median of FoxP3+ lymphocytes (p = 0.035). Similarly, SCCs of the lower lip with well-delineated infiltrating borders or arranged in solid cords, bands and/ or strands showed greater median of FoxP3+ lymphocytes compared to tumors arranged in small groups (p = 0.003). No statistically significant differences were observed in the amount of FoxP3+ lymphocytes in relation to the degree of keratinization (p = 0.525) and the degree of nuclear pleomorphism (p = 0.343) in the lesions. The results of this study suggest the involvement of Treg cells in the modulation of immune and inflammatory responses in the microenvironment of SCCs of the lower lip. The role of these cells may be more important in the initial stages than in the advanced stages of lip carcinogenesis.